Ethical dilemmas in scientific publication: pitfalls and solutions for editors - Gollogly, Laragh; Momen, Hooman (Revista de Saúde Pública, 2006)
Editors of scientific journals need to be conversant with the mechanisms by which scientific misconduct is amplified by publication practices. This paper provides definitions, ways to document the extent of the problem, and examples of editorial attempts to counter fraud. Fabrication, falsification, duplication, ghost authorship, gift authorship, lack of ethics approval, non-disclosure, 'salami' publication, conflicts of interest, auto-citation, duplicate submission, duplicate publications, and plagiarism are common problems. Editorial misconduct includes failure to observe due process, undue delay in reaching decisions and communicating these to authors, inappropriate review procedures, and confounding a journal's content with its advertising or promotional potential. Editors also can be admonished by their peers for failure to investigate suspected misconduct, failure to retract when indicated, and failure to abide voluntarily by the six main sources of relevant international guidelines on research, its reporting and editorial practice. Editors are in a good position to promulgate reasonable standards of practice, and can start by using consensus guidelines on publication ethics to state explicitly how their journals function. Reviewers, editors, authors and readers all then have a better chance to understand, and abide by, the rules of publishing.